DNA methylation in disease: Immunodeficiency, Centromeric instability, Facial anomalies syndrome - Vukic, Maja (Essays Biochem, 2019)
DNA methylation is an epigenetic modification essential for normal mammalian development. Initially associated with gene silencing, more diverse roles for DNA methylation in the regulation of gene expression patterns are increasingly being recognized. Some of these insights come from studying the function of genes that are mutated in human diseases characterized by abnormal DNA methylation landscapes. The first disorder to be associated with congenital defects in DNA methylation was Immunodeficiency, Centromeric instability, Facial anomalies syndrome (ICF). The hallmark of this syndrome is hypomethylation of pericentromeric satellite repeats, with mutations in four genes: DNMT3B, ZBTB24, CDCA7 and HELLS, being linked to the disease. Here, we discuss recent progress in understanding the molecular interactions between these genes and consider current evidence for how aberrant DNA methylation may contribute to the abnormal phenotype present in ICF syndrome patients.